(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2025)
This study deals with the phenomenon of Cryptocurrency after their importance in the field of financial investment has increased, and their impact on the global financial system and monetary policies has worsened from central banks and regulatory and supervisory organisations in the Arab countries, as well as evaluating and analyzing the positions of Arab countries on these currencies, and the efforts of some Arab countries to issue central digital currencies as a significant alternative to Cryptocurrency. The study also contains a trade-off based on objective grounds between the two options of regulation and prohibition of these currencies at the level of Arab countries.